PCAT1/miR-129/ABCB1 axis confers chemoresistance in non-small cell lung cancer - Ruifen Tian (Frontiers in Bioscience-Landmark, 2020)
Long noncoding RNA prostate cancer-associated transcript 1 (PCAT1) is oncogenic and causes progression of non-small cell lung cancer (NSCLC). We hypothesized that PCAT1 might be involved in the acquisition of chemoresistance of NSCLC cells to treatment with cisplatin (DDP). Here, we show that PCAT1 and ATP-binding cassette sub-family B member 1 (ABCB1) are highly expressed in NSCLC tissues and cell lines, and regulate the growth and apoptosis of these cells. Compared with those in DDP-sensitive patients, PCAT1 and ABCB1 are highly expressed in the tumors of DDP-resistant patients, and such overexpression correlates with a shorter overall survival of these patients. Knockdown of PCAT1 or upregulation of miR-129 led to apoptosis and sensitized the DDP-resistant cells to DDP. The 3’ UTR activity of PCAT1 and ABCB1, which was increased by PCAT1 overexpression, was shown to harbor an miR-129 binding site. DDP resistance is induced by elevated ABCB1 expression, which involves binding of miR-129 in DDP resistant cells. These findings suggest that the PCAT1/miR-129/ABCB1 axis may be a potential target for the treatment of DDP-resistant oat cell cancer.